KESAKSIAN PEREMPUAN DALAM TRANSAKSI MUAMALAH MENURUT AL QURAN - Khairuddin Khairuddin (Marwah: Jurnal Perempuan, Agama dan Jender, 2010)
In the al Quran explained that the testimony of two women equal to the testimony of a man. This was rejected by feminists because it felt unfair. This term is not for the weakness of the women sense, but because of that days, women lacked competence in the field of transaction of muamalah, therefore, her memory of that transaction was weak in that regard. If illat ‘urfiy such as foundation, then his condition has changed, because in this era of globalization and the information women not only engaged in the domestic sector, but also in the public sector. In the economic field, women are no longer just a participant but instead have become a business person. Thus, the knowledge in the field of economics of course no doubt anymore.